Exploring ways to support patients with noncommunicable diseases: A pilot study in Nepal during the COVID-19 pandemic. - Hanako Iwashita; Rabina Shrestha; Uday Narayan Yadav; Abha Shrestha; Deepa Makaju; Yuriko Harada; Gaku Masuda; Lal Rawal; Archana Shrestha; Biraj Karmacharya; Rajendra Koju; Haruka Sakamoto; et al. (Public Library of Science (PLoS), 2024)
Global healthcare systems have faced unprecedented strain due to the COVID-19 pandemic, with a profound impact on individuals with non-communicable diseases (NCDs), a scenario particularly pronounced in low-income countries like Nepal. This study aimed to understand the experiences of and challenges faced by patients with NCDs in Nepal during the pandemic, focusing on healthcare service availability and identifying factors affecting healthcare use, with the goal of being prepared for future emergencies. This study utilized a telephonic survey of 102 patients with NCDs and 10 qualitative interviews with healthcare providers in the Kavrepalanchok and Nuwakot districts of Nepal. We used mixed methods, with both qualitative and quantitative approaches. Specifically, multiple correspondence analysis, hierarchical cluster analysis, and classification tree analysis were used as exploratory methods. The study revealed that while 69.6% of the participants reported no difficulty in obtaining medication, other questions revealed that 58.8% experienced challenges in accessing routine medical care. Major barriers, such as fear of infection, unavailability of medicine in rural areas, and lack of transportation, were found through the qualitative interviews. Meanwhile, participants identified innovative strategies, such as telemedicine and community-based awareness programs, as potential facilitators for addressing barriers that arise during pandemic situations such as COVID-19. The COVID-19 pandemic exacerbated challenges in accessing healthcare services for patients with NCDs in Nepal. Our findings suggest the need to design and implement telemedicine services for patients with NCDs, as well as community-based programs that aim to improve health literacy, encourage healthy behavior, prevent development of NCDs, and ensure continuity of care during such crises, especially in countries with limited resources.